Mutation Spectrum in the CACNA1A Gene in 49 Patients with Episodic Ataxia - Sintas, Cèlia (Sci Rep, 2017)
Episodic ataxia is an autosomal dominant ion channel disorder characterized by episodes of imbalance and incoordination. The disease is genetically heterogeneous and is classified as episodic ataxia type 2 (EA2) when it is caused by a mutation in the CACNA1A gene, encoding the α(1A) subunit of the P/Q-type voltage-gated calcium channel Ca(v)2.1. The vast majority of EA2 disease-causing variants are loss-of-function (LoF) point changes leading to decreased channel currents. CACNA1A exonic deletions have also been reported in EA2 using quantitative approaches. We performed a mutational screening of the CACNA1A gene, including the promoter and 3′UTR regions, in 49 unrelated patients diagnosed with episodic ataxia. When pathogenic variants were not found by sequencing, we performed a copy number variant (CNV) analysis to screen for duplications or deletions. Overall, sequencing screening allowed identification of six different point variants (three nonsense and three missense changes) and two coding indels, one of them found in two unrelated patients. Additionally, CNV analysis identified a deletion in a patient spanning exon 35 as a result of a recombination event between flanking intronic Alu sequences. This study allowed identification of potentially pathogenic alterations in our sample, five of them novel, which cover 20% of the patients (10/49). Our data suggest that most of these variants are disease-causing, although functional studies are required.